2023
DOI: 10.1371/journal.pcbi.1010873
|View full text |Cite
|
Sign up to set email alerts
|

Environmental uncertainty and the advantage of impulsive choice strategies

Abstract: Choice impulsivity is characterized by the choice of immediate, smaller reward options over future, larger reward options, and is often thought to be associated with negative life outcomes. However, some environments make future rewards more uncertain, and in these environments impulsive choices can be beneficial. Here we examined the conditions under which impulsive vs. non-impulsive decision strategies would be advantageous. We used Markov Decision Processes (MDPs) to model three common decision-making tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 116 publications
0
1
0
Order By: Relevance
“…Studies have shown that individuals living in a context of economic scarcity tend to prefer immediate over delayed rewards more often than people living in wealthier conditions (Anderson et al, 2023;Griskevicius et al, 2011;Mani et al, 2013). One explanation is that preferring an immediateyet smallerreward is a good strategy when the future is too difficult to predict (Burk & Averbeck, 2023;Frankenhuis et al, 2016). This phenomenon could in part explain the higher risks of health-related problems and substance abuse in chronic poverty (Price et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that individuals living in a context of economic scarcity tend to prefer immediate over delayed rewards more often than people living in wealthier conditions (Anderson et al, 2023;Griskevicius et al, 2011;Mani et al, 2013). One explanation is that preferring an immediateyet smallerreward is a good strategy when the future is too difficult to predict (Burk & Averbeck, 2023;Frankenhuis et al, 2016). This phenomenon could in part explain the higher risks of health-related problems and substance abuse in chronic poverty (Price et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Perceived environmental uncertainty and uncertainty intolerance may affect coping styles. Previous research has demonstrated that perceived environmental uncertainty increases negative coping styles and impulsive choice strategies ( Burk and Averbeck, 2023 ). Uncertainty management theory emphasizes that individuals first evaluate environmental uncertainty and that perceptions and evaluations of environmental uncertainty have a direct effect on individual psychology and behavior ( Brashers, 2001 ).…”
Section: Introductionmentioning
confidence: 99%